Determination of the pressure in the cylinder of the automotive internal combustion engine by the installation of tensommetric sensors - Korobko, Bogdan; Vasyliev, Oleksiy; Rohozin, Ivan; Vasyliev, Ievgen (Academic journal Industrial Machine Building Civil Engineering, 2018)
The analysis of well-known methods of  displaying and their cost has made it possible to conclude that the methods of direct and indirect displaying have a number of serious shortcomings. Therefore, the diagnostic method for the condition of the internal combustion engine according to the value of gas pressure in the cylinders of the engine has been proposed. This method allows determining its indicator ratios, assessing the engine`s health of the ICE, the regulator (control) performance, efficiency and environmental cleanliness. This article describes the general principle of operation of the device and components of the process of measurement and processing of the obtained data. The authors of the article provided the connection diagram and substantiated the efficiency of the proposed method for obtaining information on internal cylinder processes. The results of the performed calculations indicate the suitability of the proposed calculation method for the simulation of internal cylinder processes inside internal combustion engines, including the modern ones
Keywords: internal combustion engine; indicator diagram; diagnostics; gas pressure; cylinder-piston group; stud; stretching